Music-Evoked Nostalgia and Wellbeing During the United Kingdom COVID-19 Pandemic: Content, Subjective Effects, and Function - Gibbs, Hannah; Egermann, Hauke (Frontiers in Psychology, 2021)
Nostalgic music is defined as that which evokes feelings of nostalgia through reminders of certain periods of life, places or people. Feelings of nostalgia are said to occur during times of hardship and difficult transitionary periods, such as the first COVID-19 lockdown in the UK in 2020. Here, the reassurance of the past might have held certainty that could sustain a sense of meaning and purpose in life and influence wellbeing. The aims of the presented study were to explore the nature of music-induced nostalgia during the lockdown, by analysing participants’ narratives conjured by the music and their emotional responses to them, and to determine the extent that using nostalgic music listening as an emotion regulation strategy had an impact on wellbeing. Data was collected by means of an online questionnaire, which retrospectively investigated nostalgic music during the lockdown. Participants listened to a self-selected piece of music that they had listened to 3 months prior which induced feelings of nostalgia, reported their resulting emotion and the content of memories associated with their nostalgia, and completed a questionnaire rating their experienced effect of nostalgia in relation to their piece of music. Following this, we investigated the functions that nostalgic music tends to have in regulating emotions through means of a pre-validated scale. 570 participants (34% identified as male) were recruited (age years M=44, SD=16). Concurrent with existing research, the findings suggest that there are significant differences in the affective and narrative content of nostalgic music listening in relation to which emotion regulation strategy was used, and that employing nostalgic music listening as a form of approaching difficult emotions can have a positive impact on wellbeing.